The role of the library association in preparing members for new trends - Osman, Z. (1986)
The significance of having members equipped to cope with new challenges has far-reaching effects on any profession and shows the direction towards which the profession is moving. Usually when one talks of the path that a profession treads, one usually means the path of professionalism. To a great extent, the process of professionalisation that a profession undergoes is facilitated by the existance of a professional association. Whether or not the occupation can become a full-fledged profession or merely assume the mantle of professionalism depends a great deal on the role the association plays in this process of professionalisation.